Benzo[de]isoquinoline-1, 3-dione condensed asymmetric azaacenes as strong acceptors. Issue 21 (4th May 2022) - Zhou, Pengxin; Deng, Lanlan; Han, Zengtao; Zhao, Xiaolong; Zhang, Zhe; Huo, Shuhui
Abstract : Three benzo[de]isoquinoline-1, 3-dione (BQD) condensed asymmetric azaacenes, BQD-TZ, BQD-AP andBQD-PA, with different end groups, have been successfully synthesized and their structures were confirmed by single-crystal X-ray diffraction. Abstract : We have designed and synthesized three novel benzo[de]isoquinoline-1, 3-dione (BQD) condensed asymmetric azaacenes, BQD-TZ, BQD-AP and BQD-PA, with different end groups of 1, 2, 5-thiadiazole, acenaphthylene and phenanthrene. The triisopropylsilylethynyl groups were grafted to increase the solubility and crystallinity of the three molecules. These molecules have high electron affinity values of 3.87, 3.69 and 3.74 eV for BQD-TZ, BQD-AP and BQD-PA, respectively as confirmed by cyclic voltammetry measurements. Single-crystal X-ray diffraction revealed that these molecules have strong π–π stacking with distances of 3.31–3.41 Å and different stacking arrangements.